The last original wife : a novel - Frank, Dorothea Benton (New York : William Morrow, 2013)
"Experience the sultry Southern atmosphere of Atlanta and the magic of the Carolina Lowcountry in this funny and poignant tale of one audacious woman's quest to find the love she deserves, from New York Times bestselling author Dorothea Benton Frank.Leslie Anne Greene Carter is The Last Original Wife among her husband Wesley's wildly successful Atlanta social set. His cronies have all traded in the mothers of their children they promised to love and cherish--'til death did them part--for tanned and toned young Barbie brides.If losing the social life and close friends she adored wasn't painful enough, a series of setbacks shake Les's world and push her to the edge. She's had enough of playing the good wife to a husband who thinks he's doing her a favor by keeping her around. She's not going to waste another minute on people she doesn't care to know. Now, she's going to take some time for herself--in the familiar comforts and stunning beauty of Charleston, her beloved hometown. In her brother's stately historic home, she's going to reclaim the carefree girl who spent lazy summers sharing steamy kisses with her first love on Sullivans Island. Along Charleston's live oak- and palmetto-lined cobblestone streets, under the Lowcountry's dazzling blue sky, Les will indulge herself with icy cocktails, warm laughter, divine temptation and bittersweet memories. Daring to listen to her inner voice, she will realize what she wants. and find the life of which she's always dreamed.Told in the alternating voices of Les and Wes, The Last Original Wife is classic Dorothea Benton Frank: an intoxicating tale of family, friendship, self-discovery, and love, that is as salty as a Lowcountry breeze and as invigorating as a dip in Carolina waters on a sizzling summer day"--
"Leslie Anne Greene Carter is the last original wife among her husband's group of cronies. They've all traded in for younger... blonder... more enhanced models. But she is proud of her status and the longevity of her marriage. Sure the spark isn't quite there the way it once was. And it would be nicer if her husband paid a bit more attention to her desires but there's something to be said for a comfortable relationship. Or at least she thinks so until one day, out golfing with her husband and his friends, she falls into a manhole. And nobody realizes that she's gone. With her eyes finally open to what her perfect life has truly become, Leslie must trust in the healing powers of South Carolina's lush beaches, beautiful sunsets, and feisty residents. The Last Original Wife is a classic tale of friendship and love dipped in the salty waters of a South Carolina summer"--
Keywords: Wives -- Fiction; Magic -- Fiction; Families -- Fiction; FICTION / Contemporary Women; FICTION / Family Life; FICTION / Humorous; Humorous fiction